Pengetahuan remaja terhadap produk “Gamboeng White Tea” di lingkungan Fakultas Pertanian Universitas Jenderal Soedirman - Rifka Hania; Kralawi Sita (Jurnal Penelitian Teh dan Kina, 2018)
Research Institute for Tea and Cinchona Gambung produces white tea with the “Gamboeng White Tea” brand. “Gamboeng White Tea” sales decreased for the last three years (2016-2018). To resolve the problem, “Gamboeng White Tea” marketing must be expanded, to enter the millennial customer market. This study aims to discover teenage customer’s knowledge about “Gamboeng White Tea” products in the market. This study used an online survey method. The data collection was carried out by a questionnaire, and the data were analyzed descriptively. The results of this study showed that: 1) most of the respondents did not know there were white tea products in markets and did not know the benefits of white tea, 2) majority of the respondents did not know about “Gamboeng White Tea” brand, and respondents also stated that the packaging of “Gamboeng White Tea” products was ordinary because the packaging was unattractive for teenage customers, and 3) majority of the respondents never consumed white tea because they did not know there were white tea products in markets.